Aspecte privind limitele rolului diriguitor la verificarea cerinţelor de formă şi conţinut ale cererii de chemare în judecată la faza intentării procesului civil - Botnari, Veaceslav (CEP USM, 2024)
The present paper aims to highlight the requirements of form and content of the civil lawsuit, identifying the problematic elements both from a doctrinal point of view and from the point of view of national judicial practice. The paper is based on regulations provided by Civil Procedure Code of Moldova, as well as studies of national and Romanian authors. The study will show some of national court decisions issued at the stage of initiation of civil proceedings regarding the form and content of the claim in the civil lawsuit, including our opinion and recommendation upon the discussed matters as well as the opinion of other national and Romanian authors.
ISSUES CONCERNING THE LIMITS OF THE COURT’S SUPERVISORY ROLE IN VERIFYING THE REQUIREMENTS AS TO FORM AND CONTENT OF A CLAIM AT THE STAGE OF INITIATION OF CIVIL PROCEEDINGS
Keywords: content; form; indentation; director; conținut; formă; intentare; diriguitor